In Vitro Propagation of Kaempferia larsenii Sirirugsa for Conservation of Rare Plant Species in Thailand - ผุดผ่อง จิราภรณ์; แสนสุข สุรพล; แสนสุข ปิยะพร (KKU Science Journal, 2015)
The tissue culture technique has been widely used for collection, propagation and preservation of rare plant species. In this study, in vitro propagation of Kaempferia larsenii Sirirugsa, a vulnerable, endemic and rare plant in Thailand was investigated. Microshoots of K. larsenii Sirirugsa were cultured on Murashige and Skoog (MS) (1962) media supplemented with various concentrations (0, 0.5, 1, 2, 3, 4 and 5 mg/l) of cytokinin (BA, Kinetin and TDZ), a combination of cytokinin (BA with Kinetin or TDZ), and MS media supplemented with various concentrations (0, 0.1, 0.5, 1, 1.5 and 2 mg/l) of auxin alone (IAA, IBA and NAA) for eight weeks to induce shoot and root formation. The maximum number of shoots was observed in the medium supplemented with 1 mg/l TDZ (6.6 shoots/explant) and the best rooting was induced in MS medium with 0.5 mg/l IAA (10.60 roots/explant).